PHOTOSYNTHETIC PERFORMANCE IN PLOIDY LEVELS AND AMPHYPLOIDS OF WHEAT DURING DEVELOPMENTAL STAGES - S. S. Bilgrami; S. A. Houshmand; M. Khodambashi; P. Zandi; M. Siavoshi; S. Khademi; S. Navabpour; M. Nasiri Dehbaneh; H. Amouei; M.R. Tadayyon; K. Sorkheh (Journal of Animal and Plant Sciences, 2015)
In order to determine the changing trends of some physiological characteristics, biological yield, and flag leaf area in wheat ploidy levels, while also comparing them with Triticale and Tritipyrum amphyploids, 23 genotypes were evaluated in a field-grown condition. Stomatal conductance (gs), net photosynthesis rate (Pn), transpiration rate (Tr), substomatal CO2 concentration (Ci), and water use efficiency (WUE) were measured through three developmental stages including tillering (Til), early grain filling (EGF) and late grain filling (LGF). Different traits in Triticale and Tritipyrum genotypes showed a significant difference in comparison with wheat ploidy genotypes. Besides, a significance difference was observed between the ploidy levels. At EGF stage, there was a considerable disparity among Triticum and Triticale amphiploids for Ci, Tr, and WUE. Triticum and Tritipyrum genotypes statistically demonstrated dissimilar, but meaningful trends in all of the assessed physiological traits except for Pn. Moreover, Triticale and Tritipyrum amphiploids represented to have various results in terms of gs. Results showed that the amounts of gs, Pn, and WUE have increased noticeably until EGF stage and they have declined by 50% at LGF stage. The highest mean values corresponding to Ci (Til, EGF, LGF), Pn (LGF), Tr (EGF), and gs (EGF, LGF) traits were belonged to Tritipyrum species which likely relates the breeding capability of such newfound amphiploid genotypes. Correlation coefficients analysis revealed that Pn had positive association with gs and Tr in the Til and LGF stages. Throughout the whole phases of the study, Tr and WUE have increased with increasing gs and Pn. Reductions of gs and Tr in EGF stage have caused WUE to increase. In 4x and 6x wheat genotypes, the biological yield was positively associated with Pn and Tr. In 4x wheat, the flag leaf area had a negative correlation with Pn and WUE, while in 6x wheat, along with the flag leaf area increasing, Pn and Tr have soared and Ci has decreased. This research was an attempt to assist wheat breeders in selecting well-suited breeding lines and physiological parameters, leading to producing high-yielding genotypes in Triticum spp.
Keywords: Developmental stages; photosynthesis performance; physiological responses; Triticum spp